Analisis Sanksi Pidana terhadap Pelaku Penyebaran Hoaks di Media Sosial berdasarkan UU ITE dan KUHP - Tanujaya, Antonyo Hartono; Amsori, Amsori; Nugroho, Meysita Arum (HUMANIORUM, 2025)
This scientific article analyzes the criminal sanctions against perpetrators of hoax dissemination on social media based on the Electronic Information and Transactions Law (UU ITE) and the Criminal Code (KUHP) in Indonesia. This research employs a normative legal research approach to examine the provisions within both legal instruments. The results indicate that the UU ITE generally provides more severe sanctions compared to the KUHP for the crime of spreading hoaxes, particularly in the context of electronic transactions and hate speech. Nevertheless, the effectiveness of these criminal sanctions in preventing the spread of hoaxes remains debatable, and this study concludes that a more comprehensive approach involving legal, educational, and technological aspects is necessary.